DEAD-box RNA helicase is dispensable for mitochondrial translation in Trypanosoma brucei - Richterová, Lenka; Vávrová, Zuzana; Lukeš, Julius (Experimental parasitology, 2011)
DEAD-box RNA helicase, a putative subunit of the mitochondrial ribosome of Trypanosoma brucei, has been down-regulated in the procyclic and bloodstream stage by RNA interference. Although ablation of the transcript leads to a week growth phenotype in the procyclic cells, the protein does not seem to be essential for mitochondrial translation under standard cultivation conditions, as shown by an assay that allows visualization of the de novo synthesized proteins. Furthermore, we show that synthesis of cytochrome c oxidase subunit I and cytochrome b does not occur in the mitochondrion of the bloodstream stage.
Keywords: RNA Interference; Ribosomes; mitochondrie; ribozomy; Trypanosoma brucei brucei; respirační komplex IV; cytochromy b; proteosyntéza; RNA interference; Electron Transport Complex IV; Mitochondria; Cytochromes b; DEAD-box RNA-helikasy; DEAD-box RNA Helicases; Protein Biosynthesis